Word Formation of New Terms in Adobe Photoshop Program: Implication for the Teaching English Vocabulary - Ahmad Takhfif; Rohmani Nur Indah; Galuh Nur Rohmah (Loquen, 2021)
The development of technology may impact educational field. Research on technology and language learning shows that technology may provide some opportunities for students to get an easy access in information, integrated learning, and easy way to practice what they learn. The language created in the computer program can be used as a communication tool for its application, including in teaching English. Nowadays, using computer can support language learning. Regarding this point, this study aims to analyze new terms found in Adobe Photoshop Program. Further, the researchers also described morphological processes of the new terms in Adobe Photoshop program in teaching English vocabulary. While, the design of this research is descriptive qualitative design. The result shows compound and derived words can be classified as new terms in Adobe Photoshop CS4. Related to teaching vocabulary, the results show that teaching English vocabulary through word formation found in new terms in Adobe Photoshop Program may give an impact on students’ vocabulary development.